2016
DOI: 10.21603/2078-8975-2016-3-38-44
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Health of Professional Athletes Involved in Extreme Sports

Abstract: Аннотация: Предметом настоящего исследования было изучение психологического здоровья спортсменов-профессионалов, которые занимаются экстремальными видами спорта. Цель исследования: установить влияние занятий экстремальными видами спорта на психологическое здоровье спортсменов-профессионалов. В иссле-довании приняли участие 168 спортсменов-профессионалов, которые занимаются автогонками, дзюдо, каратэ, альпинизмом, рукопашным боем и боксом. Из них было сформировано 2 группы: основная (n = 80), куда вхо-дили проф… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…A similar effect of certain external factors on the psychological state of athletes was also observed (Alyoshicheva, 2016). This study found a high level of anxiety among professional athletes in extreme sports before the competition.…”
Section: Discussionsupporting
confidence: 83%
“…A similar effect of certain external factors on the psychological state of athletes was also observed (Alyoshicheva, 2016). This study found a high level of anxiety among professional athletes in extreme sports before the competition.…”
Section: Discussionsupporting
confidence: 83%
“…Especially at the beginning, research has focused on arguing for the negative effects depending on several variables, (gender, age, sports, etc) at physical level: high risk-taking levels produce lesions and even death [16,24,26,37], sleep disturbances [28], but also pathological personality disorders (narcissism, anxiety, neuroticism, addictions), corelated with compulsive and deviant behaviours (pathological abuse and addiction to drugs, alcohol, sport) [2], [14,15], [29], [38]. Recent studies have focused on the benefits on physical performance, mental health, and personality traits, on emotion management -courage, humility, fear [7,8], [10], [27], [40], [46], physical, emotional, and mental freedom [9], psychological recovery and emotional well-being [3], [25] even among people suffering from hyperkinetic disorders (ADHD) [42], self-control and stress management, self-knowledge and self-achievement [12], [21], [23], [31,32].…”
Section: The Consequences Of Extreme Sports Developmentmentioning
confidence: 99%
“…Extreme training loads often lead to mental exhaustion, increase professional stress, and reduce quality of life. 19 , 20 Professional athletes are expected not only to propagate a particular sport but also a socially desirable, goal-oriented, active lifestyle. Many educators recognize the enormous educational potential of professional athletes and thus emphasize the development of Olympic education programs.…”
Section: Introductionmentioning
confidence: 99%